2020
DOI: 10.24095/hpcdp.40.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoke exposure and sleep: estimating the association of urinary cotinine with sleep quality

Abstract: Introduction A majority of studies on tobacco smoke exposure and sleep quality have relied on self-reported smoking, resulting in potential exposure misclassification and biases related to self-report. The objective of this study was to investigate associations between urinary cotinine, a biological marker of tobacco smoke exposure, and sleep quality measures, including sleep duration, sleep continuity or efficiency, sleep satisfaction and alertness during normal waking hours. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Another noteworthy point in this study is that the ORs for poor sleep quality related to smoking status in female were greater than those for male in all age groups. Differences by sex concerning the sensitivity and metabolization rate of nicotine may explain the stronger association between tobacco smoke exposure and poorer sleep quality among female [ 13 ]. In a study that included twins as the subjects, the clearance of nicotine and cotinine, the nicotine-to-cotinine clearance ratio, and the ratio of trans-3 ′-hydroxycotinine to cotinine were significantly higher in female than in male.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another noteworthy point in this study is that the ORs for poor sleep quality related to smoking status in female were greater than those for male in all age groups. Differences by sex concerning the sensitivity and metabolization rate of nicotine may explain the stronger association between tobacco smoke exposure and poorer sleep quality among female [ 13 ]. In a study that included twins as the subjects, the clearance of nicotine and cotinine, the nicotine-to-cotinine clearance ratio, and the ratio of trans-3 ′-hydroxycotinine to cotinine were significantly higher in female than in male.…”
Section: Discussionmentioning
confidence: 99%
“…Given the strong effect of psychological factors on sleep quality, the results of 2 models (2 types of adjusted odds ratios [aORs]) were presented depending on whether these factors were included. Because of the differences in the metabolic processes related to nicotine and cotinine and in the relationship between sleep quality and tobacco smoking according to sex and age [ 10 , 13 , 20 ], we performed separate analyses stratified by sex and age group to explore the potential effects on the association between cigarette smoking and sleep quality. An interaction model was used to estimate the effect of smoking on sleep quality according to age.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies used biomarkers for differentiating smoking exposure, and those using biomarkers for evaluating smoking intensity reported inconsistent results. A Canadian national survey reported that increasing urinary cotinine levels were associated with higher odds of disturbed sleep quality 7 . In contrast, a German study using the Pittsburgh Sleep Quality Index (PSQI) showed no significant associations between smoking intensity measured by biological indicators (i.e.…”
Section: Introductionmentioning
confidence: 99%